Angola : Oil, Broad-Based Growth, and Equity - World Bank (Washington, DC: World Bank, 2012)
This book points out that the main issues confronting the Angolan authorities in their efforts to consolidate macroeconomic stability on a sustainable basis and in promoting an improvement in the welfare of the Angolan citizens do not seem to differ significantly from those addressed in the 1990 report. Therefore, in the current Country Economic Memorandum, the Bank reassesses some of the key issues that remain relevant nowadays and that should help the Angolan economy reach a path of sustainable economic development. The analysis in this report centers around the following four core issues: (i) taking stock of socio-economic realities; (ii) the options available for the management of the country's mineral wealth without deleterious macroeconomic consequences; (iii) the main constraints to economic diversification away from the mineral sectors; and (iv) the challenges and opportunities to improve the welfare of the population. Each of these core issues forms the building blocks that provide an overview of the current situation and a possible solution to Angola's structural problems in the short to the medium term. The report thus plays an informative role and offers policy recommendations. In Chapter 1, the analysis starts with a brief discussion of socio-economic realities in the country. In Chapter 2, a comprehensive macroeconomic assessment is presented highlighting major past features, the country's constant search for stability, and recent successes in the macroeconomic front. In Chapter 3, the report discusses the structure of the petroleum sector, the future production profile, the size of the oil wealth, and policy options to manage the revenue windfall. Chapter 4 focuses on the diamond sector, its structure, legal and fiscal framework, and explores ways in which the sector can improve its contribution to social development. In Chapter 5, the report assesses the quality of the business environment and the opportunities to improve the investment climate. Chapter 6 discusses alternatives to unleash the potential of the agricultural sector in generating employment outside of the mineral sectors. Finally in Chapter 7, the analysis focuses on how to improve the livelihoods of the poor and of the vulnerable with recommendations on how to use the mineral wealth to improve public service delivery targeted to the poor.